Crowdfunding Misuse as Cybercrime: A Criminal Law Perspective in Indonesia - Nugraha Pranadita; Sungguh Raja Sembiring; Heddy Permana Putra; Yuninda Dwi Kartika; Yoga Gustiadi; Gede Indra Udayana (Civiliza Publishing, 2026)
The rapid development of information technology has led to various innovations in the digital financial sector, one of which is crowdfunding. In principle, crowdfunding is a legitimate fundraising mechanism that provides social and economic benefits. However, in practice, crowdfunding is often misused as a means to commit cybercrime. Such misuse includes fictitious fundraising, misleading information, and the misappropriation of funds collected from the public. This study aims to analyze crowdfunding as a form of cybercrime from the perspective of Indonesian criminal law. The research employs a normative legal method using statutory and conceptual approaches. The findings indicate that unlawful crowdfunding practices may fulfill the elements of criminal offenses, both as conventional fraud and as electronic-based crimes, thereby giving rise to criminal liability for perpetrators, including corporate entities. Therefore, stronger supervision, effective law enforcement, and enhanced digital legal literacy are essential to ensure legal protection for the public.